2016
DOI: 10.1097/meg.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of faecal calprotectin and small bowel capsule endoscopy and their correlation in suspected isolated small bowel Crohn’s disease

Abstract: FC performs modestly as a screening test to exclude small bowel inflammation. However, we recommend interpretation within the overall clinical context to avoid overlooking the infrequent patient with small bowel inflammation and a negative FC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Most studies reported higher FC concentrations in CD patients than in those with normal small bowel findings or other disease conditions, but not always a significant association with CE findings …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Most studies reported higher FC concentrations in CD patients than in those with normal small bowel findings or other disease conditions, but not always a significant association with CE findings …”
Section: Resultsmentioning
confidence: 91%
“…Considerable variability was observed among different cohorts of patients using the same FC cutoff (50 μg/g), with values of the sensitivity, specificity, PPV, and NPV being, respectively, 59–88.9%, 23–71%, 14.3–56%, and 83–94.1% …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations